Pentecostal and Charismatic Spiritualities and Civic Engagement in Zambia - M'fundisi-Holloway, Naar (Christianity and Renewal - Interdisciplinary Studies, 2018)
For the past sixty years, the Pentecostal and Charismatic movement has played a major role in Zambia. In this book, Naar Mfundisi-Holloway explains the history of this development and its impact on civic engagement. She opens a discussion on church-state relations and explains how the church presented a channel of hope in the wake of the HIV/AIDS pandemic, despite having a history that eschewed civic engagement. In fact, the pandemic propelled the church to work alongside the state in the fight against the disease. Using interviews and historical analysis, this book provides valuable insight into how Pentecostal and Charismatic churches have effectively engaged matters of civic concern in Zambia dating from colonial times.